The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jfda.2013.09.013
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a health-promoting school program to enhance correct medication use in Taiwan

Abstract: This study was an evaluation of the Health Promoting School (HPS) program in Taiwan and its effectiveness in enhancing students’ knowledge and abilities with regard to correct medication usage. In 2011, baseline and follow-up self-administered online surveys were received from 3520 middle-school and primary students from intervention schools, and 3738 students from comparison primary and secondary schools completed the same survey. The results indicated that after implementing the correct medication use HPS pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(20 reference statements)
0
9
0
2
Order By: Relevance
“…Since the improvement of medication literacy could enhance an individual’s ability to properly use medication [ 33 ], medication literacy enhancement programs should be developed and implemented in schools and communities. Studies have shown that education programs on correct medication use could improve medication knowledge among adolescents [ 33 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the improvement of medication literacy could enhance an individual’s ability to properly use medication [ 33 ], medication literacy enhancement programs should be developed and implemented in schools and communities. Studies have shown that education programs on correct medication use could improve medication knowledge among adolescents [ 33 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study’s questionnaire was developed and modified according to those presented by previous studies [ 33 , 55 , 56 ]. Its content validity was assessed by a diverse expert panel comprising two family medicine physicians; seven pharmacists (three community pharmacists, three hospital pharmacists, and one policy developers); four public health educators; and two school teachers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This healthy behavior might be attributed to the fact that the incidence of diseases necessitating long-term use of medications in this phase of life is low. In agreement with this, Chi et al (2013), in a study in Taiwan reported that <10% of the students reported that they would buy or obtain medication according to family or friends or traditional therapists' recommendations.…”
Section: Discussionmentioning
confidence: 60%
“…Studies in Taiwan (Table 2) evaluated the correct medicines arm of the Health Promoting School (HPS) Program. This partnership between educators and pharmacists was launched in 2011 in 14 cities 16 . Study interventions included direct teaching, posters, student outreach and pharmacist guest speakers.…”
Section: Resultsmentioning
confidence: 99%